Thrombosis Complications in Pediatric Acute Lymphoblastic Leukemia: Risk Factors, Management, and Prevention: Is There Any Role for Pharmacologic Prophylaxis? - Rodriguez, Vilmarie (Frontiers in Pediatrics, 2022)
Pediatric acute lymphoblastic leukemia (ALL) has achieved close to 90% cure rates through extensive collaborative and integrative molecular research, clinical studies, and advances in supportive care. Despite this high achievement, venous thromboembolic complications (VTE) remain one of the most common and potentially preventable therapy-associated adverse events in pediatric ALL. The majority of thromboses events are venous and involve the upper central venous system related to the use and location of central venous catheters (CVC), with reported rates of symptomatic and asymptomatic venous-catheter-related VTE of 2.6-36.7% and 5.9-43% respectively. Thrombosis can negatively impact not only disease-free survival [e.g., therapy delays and/or interruption, omission of chemotherapy agents (e.g., asparaginase therapy)] but also can result in long-term adverse effects that can impair the quality of life of ALL survivors (e.g., post-thrombotic syndrome, central nervous system (CNS)-thrombosis related complications: seizures, neurocognitive deficits). In this review, will discuss thrombosis pathophysiology in pediatric ALL, risk factors, treatment, and prevention strategies. In addition, the recently published efficacy and safety of direct oral anticoagulants (DOACs) use in pediatric thrombosis treatment and its potential role in primary/secondary thrombosis prevention in pediatric patients with ALL will be discussed. Future clinical trials involving the use of these novel oral anticoagulants should be studied in pediatric ALL not only for primary thrombosis prevention but also in the treatment of thrombosis and its secondary prevention. These future research findings could potentially extrapolate to VTE prevention strategies in other pediatric cancer diagnoses and children considered at high risk for VTE.